A "Natural" Proposal for Addressing Climate Change. Issue 3 (4th September 2014) - Lovejoy, Thomas E.
<x content-type="archive" xml:space="preserve">Abstract</x> One of the fundamental challenges of climate change is that we contribute to it increment by increment, and experience it increment by increment after a considerable time lag. As a consequence, it is very difficult to see what we are doing to ourselves, to future generations, and to the living planet as a whole. There are monumental ethical issues involved, but they are obscured by the incremental nature of the process and the long time frame before reaching the concentration of greenhouse gases and the ensuing accumulation of radiant heat—and consequent climate change—that ensues.